2004
DOI: 10.1037/0022-3514.87.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Goal and Personality Trait Development in Emerging Adulthood.

Abstract: The present research examined continuity and change in the importance of major life goals and the relation between change in goals and change in personality traits over the course of college (N = 298). Participants rated the importance of their life goals 6 times over a 4-year period and completed a measure of the Big Five personality traits at the beginning and end of college. Like personality traits, life goals demonstrated high levels of rank-order stability. Unlike personality traits assessed during the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
226
4
16

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(275 citation statements)
references
References 46 publications
25
226
4
16
Order By: Relevance
“…Furthermore, traits showed little overall relation to growth goals. Altogether, these findings contribute to the mounting evidence that narratives are not merely derivatives of traits (Bauer & McAdams, 2004b;Bauer et al, 2005aBauer et al, , 2005bLodi-Smith et al, 2009;Roberts et al, 2004; see also . In other words, one cannot infer a person's life story and identity from his or her broad personality traits (McAdams, 1995), particularly in terms of how the life story relates to psychosocial maturity and SWB.…”
Section: Narrative Growth Goals As Predictors Of Eudaimonic Growthmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, traits showed little overall relation to growth goals. Altogether, these findings contribute to the mounting evidence that narratives are not merely derivatives of traits (Bauer & McAdams, 2004b;Bauer et al, 2005aBauer et al, , 2005bLodi-Smith et al, 2009;Roberts et al, 2004; see also . In other words, one cannot infer a person's life story and identity from his or her broad personality traits (McAdams, 1995), particularly in terms of how the life story relates to psychosocial maturity and SWB.…”
Section: Narrative Growth Goals As Predictors Of Eudaimonic Growthmentioning
confidence: 86%
“…Moreover, the Big Five traits are often considered to be the basic building blocks of personality, with personality characteristics such as goals and narratives being mere epiphenomena (e.g., McCrae & Costa, 1999). Yet narratives consistently predict indices of psychological health and well-being beyond the effects of broad personality traits (Bauer & McAdams, 2004b;Bauer et al, 2005aBauer et al, , 2005bMcLean & Pratt, 2006;Roberts, O'Donnell, & Robins, 2004), even longitudinally (Lodi-Smith, Geise, Roberts, & Robins, 2009). In an extension of Hypothesis 2, we expected that narrative growth goals would be independent of broad personality traits in predicting facets of eudaimonic growth.…”
Section: Personality Traitsmentioning
confidence: 99%
“…Furthermore, changes in goal importance over a four-year period were related to changes in personality traits, mimicking the baseline pattern (Roberts et al, 2004). Similarly, another study found extraversion to be modestly related to life goals, whereas neuroticism was virtually unrelated to any life goal domain (Roberts & Robins, 2000).…”
mentioning
confidence: 94%
“…Moreover, reciprocal effects models revealed effects of prior personality traits on subsequent life goal importance, but almost no effects of prior life goal importance on subsequent personality traits (Lüdtke et al, 2009). Other longitudinal results revealed modest correlations between extraversion and goal importance, whereas neuroticism was unrelated to any of the goal domains at baseline (Roberts, O'Donnell, & Robins, 2004).…”
mentioning
confidence: 99%
“…Second, goals are linked to prospective memory tasks that promote their fulfillment. That is, prominent goal models (e.g., Austin and Vancouver 1996;Kruglanski 1996) view goals as embedded in a hierarchically organized associative network with life goals (e.g., learn as much as possible) at the highest end (Roberts et al 2004), midlevel goals (e.g., get a Ph.D.) in the middle (Emmons 1989;Little 1983;Markus and Nurius 1986), and intentions or prospective memory tasks (e.g., remember to work for two hours tomorrow on my dissertation) at the lowest end (e.g., Sheeran et al 2005b;Penningroth and Scott 2007). Supporting this view, there is evidence that goals produce top-down activation that boosts the accessibility and performance of related activities and intentions (Fishbach et al 2004;Sheeran et al 2005b).…”
Section: Introductionmentioning
confidence: 99%